Sacramental Suffering: The Friendship of Flannery O’connor and Elizabeth Hester - Wood, Ralph C. (Modern theology, 2008)
As the only orthodox Christian writer the American nation has yet produced, Flannery O’Connor created a remarkable body of fiction rooted in a profoundly sacramental theology. The depth of O’Connor's sacramentalism has recently been revealed with the opening of her remarkable letters to Elizabeth Hester, her most important epistolary friend. Their eleven-year correspondence centers upon two inseparable matters: conversion and suffering. The aim of this essay is to explore how the gift (or refusal) of faith comes through the embrace (or rejection) of a participation in God's own life through a life of sacramental suffering.